(untitled) (Hoboken, N.J., 2004)
This comprehensive reference, edited by one of the leading experts in the field, assimilates the newest and most effective treatment techniques for the personality disorders. Each chapter is written by scholars in the leading theoretical models: Cognitive-Behavior Therapy, Humanistic, and Integrative. Numerous detailed case examples and case studies are integrated and used throughout.
Keywords: Personality disorders,Rối loạn nhân cách; Treatment,Điều trị